2020
DOI: 10.11591/eei.v9i3.2006
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and student readiness using E-learning and M-learning

Abstract: This research is about the readiness of teachers and students to develop E-learning and M-learning for the learning process. Before developing and implementing an E-learning and M-learning system, it is important to ensure the user's readiness for the technology. Users' perceptions will affect their willingness and readiness to use the system. This study aims to investigate the teachers and students perceptions about E-learning and M-learning, ensuring their readiness to involve in developing online learning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The success of e-learning depends on a number of external and internal factors. External factors include the establishment of learning environment where teacher-student interactions are connected during the use of the information and communication technology (Meyer et al, 2008b) and the readiness of students, parents, and schools (Ramadiani et al, 2021). Internal factors include cognitive abilities: memory and attention, problem-solving, metacognitive skills, affective skills (Meyer et al, 2008b), independence, talent, and motivation (Suryabrata, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The success of e-learning depends on a number of external and internal factors. External factors include the establishment of learning environment where teacher-student interactions are connected during the use of the information and communication technology (Meyer et al, 2008b) and the readiness of students, parents, and schools (Ramadiani et al, 2021). Internal factors include cognitive abilities: memory and attention, problem-solving, metacognitive skills, affective skills (Meyer et al, 2008b), independence, talent, and motivation (Suryabrata, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was necessary to manage good learning online and pay attention to network aspects because not all students had good internet access. An investigation by Ramadiani et al [53] of junior and senior high school students in Samarinda showed that students were ready to learn online. Still, they hoped to add the use of games and music to online learning activities.…”
Section: Student Preparednessmentioning
confidence: 99%
“…At this stage, the initial game design stage will be carried out, such as creating stories, game rules, determining the software to be used, creating and finding assets, making level designs, game displays, in-game items, and in-game buttons [26][27][28].…”
Section: Pre-productionmentioning
confidence: 99%
“…The game will be tested by the developer using the Blackbox testing method to see if the various scenarios and functions in the game are running properly. Testing is carried out using the blackbox testing method that focuses on the user's perspective and divided into testing Blackbox UI main menu (Table II), testing Blackbox UI gameplay (Table III), testing Blackbox gameplay scenario (Table IV), and testing for the device (Table V) [26][27][28][29][30].…”
Section: A Blackbox Testingmentioning
confidence: 99%